SISTEM INFORMASI IDENTIFIKASI PENJEMPUTAN PADA SEKOLAH KHARISMA MAKASSAR - Jihan Novianti Putri; Arfan Yunus; Ahyar Muawwal (STMIK KHARISMA Makassar, 2019)
Children often serve as the object of the crime of abduction, violence, and abuse. The mode of the kidnapping which are often done by the perpetrators by pretending to be a guardian, relative, or family for the child from the school still difficulty in identifying their relatives. The system pick-up school children at the school are still manual charisma where the process that is using their relatives as identity card to pick up. By using the identification card as an identity can still potentially lose cards or forget to bring an identity card as well as the identity of their relatives to abuse. Therefore to increase security on the students at the school that is implementing a system of identification upon arrival by utilizing technologies already existing identification at this time. This research is intended to implement an identification system pick-up students in makassar charisma school where the identification technology in use is the fingerprint.Fingerprint is a tool that is used as the identifier of a person's identity through a fingerprint of the person so that by applying the tool identification in kindergartens can reduce identity abuse because everyone has fingerprints different finger and can increase security on the student in school.By implementing a system of identification of students at school pick-up makassar charisma can increase security and provide convenience for school parties in identifying their relatives.